Possibilities of modeling of milk formulas composition by adding functional nutrients - O. L. Lukoyanova; T. E. Borovik; T. V. Bushueva; N. G. Zvonkova; N. N. Semenova; V. A. Skvortsova; T. N. Stepanova (Вопросы современной педиатрии, 2013)
The data on necessity of certain functional nutrients adding to the composition of milk formulas, technological difficulties of their isolation and innovative methods used in this field are shown in the article. Aim: to study tolerance to investigated milk formulas and to evaluate their influence on physical development of infants younger than 1 year. Patients and methods: the results of the clinical observation of 60 healthy children (36 girls and 24 boys) at the age younger than 1 year old fed with the studied dry adapted milk formulas are shown. Criteria of feeding efficacy were: evaluation of the tolerance to the formulas, dynamics of height and weight values, results of clinical blood sample, feces microscopy as well as protein efficacy coefficient. Results: the authors established good tolerance to the studied products, appropriate improvement of height and weight values, accordance of the results of clinical blood samples to the mean age norms, absence of pathological changes in coprological tests in all of the observed children during the whole follow-up. Conclusions: the investigated formulas have optimal balanced composition of nutrients, positive influence on physical development and are well-tolerated by children, which make possible their usage in feeding of infants who cannot be breast-fed.